Prosedur Penerbitan PHQC dan Ship Health Book pada Kapal MT. Venus di Pelabuhan Kuala Tanjung oleh PT. Seroja Jaya Agensi - Onesimus Pardede; Suratni Ginting; Meriah Kita Deliani (Jurnal Bisnis Kreatif dan Inovatif, 2025)
Procedures for Issuing Port Health Quarantine Clearance (PHQC) and Ship Health Book for the MT. Venus Ship at Kuala Tanjung Port by PT. Seroja Jaya Agensi. Every ship entering the port must be in good health, free from disease outbreaks and pests. Issuance of ship health documents is the responsibility of the Health Quarantine Agency (BKK). PT. Seroja Jaya Agensi, as the agency company, acts on behalf of the ship owner in processing ship health documents at Kuala Tanjung Port. This study aims to determine the procedures for issuing Port Health Quarantine Clearance (PHQC) and Ship Health Book for the MT. Venus Ship. The procedure begins with the ship agent submitting an application to the BKK, followed by a sanitation inspection by health officers, issuance of a Certificate of Free Practice (CoP), and recording or issuing the ship health book. These documents are the primary requirements for the ship's clearance process. The research methods used were field research and library research. The results showed that the document issuance procedure involved close coordination between the ship's agent and relevant agencies, and required careful attention to the completeness and validity of the ship's documents.